Pemanfaatan Eco-enzyme ramah lingkungan bersama kelompok Pencinta Alam Bahari (PAB) Kelurahan Pangkalan Sesai Kota Dumai - Dessy Yoswaty; Rifardi Rifardi; Mubarak Mubarak; Elizal Elizal (Unri Conference Series: Community Engagement, 2021)
The role of housewives (Mitra Pengcinta Alam Bahari/PAB) contributes to the production of organic waste from cooking activities in the kitchen. For example, organic waste from vegetable residues, fruit (such as fruit peels, hard vegetable stems and leaves) and food waste. The problems faced are: the unknown technique of making eco-enzyme products to reduce pollution of environmentally friendly organic waste. One of the organic waste management techniques is the use of eco-enzyme products. The purpose of the activity is to increase the production capacity of eco-enzyme to be able to reduce organic waste pollution and to increase the entrepreneurial spirit of PAB partners to produce eco-enzyme products. The methods used are lectures, discussions and the practice of making eco-enzymes involving 20 PAB members. The results of the activity showed that PAB members were very supportive and motivated, as many as 53.0% (Strongly Agree), 42.4.0% (Agree) and 4.50% (Neutral) were willing to practice environmentally friendly eco-enzyme product utilization techniques. The results of the economic analysis of the production of 5 bottles/day of eco-enzyme products (@ Rp. 30.000,-) will generate a profit of Rp. 2,958,720/month. This provides added value for people's income and efforts to manage organic waste.